2013
DOI: 10.1371/journal.ppat.1003220
|View full text |Cite
|
Sign up to set email alerts
|

Increased CD8+ T Cell Response to Epstein-Barr Virus Lytic Antigens in the Active Phase of Multiple Sclerosis

Abstract: It has long been known that multiple sclerosis (MS) is associated with an increased Epstein-Barr virus (EBV) seroprevalence and high immune reactivity to EBV and that infectious mononucleosis increases MS risk. This evidence led to postulate that EBV infection plays a role in MS etiopathogenesis, although the mechanisms are debated. This study was designed to assess the prevalence and magnitude of CD8+ T-cell responses to EBV latent (EBNA-3A, LMP-2A) and lytic (BZLF-1, BMLF-1) antigens in relapsing-remitting M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
142
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(159 citation statements)
references
References 65 publications
7
142
0
10
Order By: Relevance
“…[ [21][22][23] The pathophysiology of EBV reactivation remains uncertain. Recent data suggest that EBV could trigger inflammatory process through interleukin-6 modulation.…”
Section: Discussionmentioning
confidence: 99%
“…[ [21][22][23] The pathophysiology of EBV reactivation remains uncertain. Recent data suggest that EBV could trigger inflammatory process through interleukin-6 modulation.…”
Section: Discussionmentioning
confidence: 99%
“…The extent of genotype intraindividual variability proved to be high in both patients and controls with a greater occurrence of coexisting alleles in patients, possibly accounted for by the known higher rate of EBV reactivation in MS. 26,27 Our study demonstrates the appropriateness of deep-sequencing platforms to investigate patterns of genetic variation of a virus that latently infects peripheral blood cells at a very low frequency. Next-generation sequencing proved to be sensitive to such an extent that when used to study the EBV genotype in immune infiltrates microdissected from postmortem brain samples of a patient with secondary progressive MS (see appendix e-1), it allowed identification of a sequence of the EBNA2 allele 1.1 and related variants (table e-3) that was not detected using a conventional sequencing method.…”
mentioning
confidence: 89%
“…Several epidemiological studies have suggested that Epstein-Barr virus (EBV) is one of the strongest candidates for this infectious agent [56][57][58] and EBV proteins and RNA have been detected in B-cells in the meninges and perivascular spaces of MS cases with extensive meningeal infiltrates and cortical demyelination [59][60][61] . It has been proposed that failure to control latent EBV infection in an immune privileged site, such as the subarachnoid space, could lead to recurrent intrathecal reactivation of EBV and tissue damage in the nearby grey matter 62,63 . However, a number of other studies have been unable to detect EBV in the brain or lesions of MS patients 64,65 and this remains a highly debated controversy 66 .…”
Section: Inflammatory Grey Matter Damagementioning
confidence: 99%